Novel Amplicon-Based Whole Genome Sequencing for Toscana Virus – A Breakthrough in Genome Analysis of a Neglected Virus in the Mediterranean Basin - Miss Martina Brandolini; Mr Giorgio Dirani; Ms Silvia Zannoli; Dr Alessandra Mistral De Pascali; Ms Ludovica Ingletto; Ms Laura Dionisi; Ms Claudia Colosimo; Prof Monica Cricca; Prof Alessandra Scagliarini; Prof Vittorio Sambri (International Journal of Infectious Diseases)
Introduction: Toscana virus (TOSV, Phlebovirus genus) is a neurotropic sandfly-transmitted virus whose distribution encompasses various countries within the Mediterranean basin. TOSV infection remains a non-notifiable disease in Europe with no official surveillance plans in place despite being considered a significant public health concern in Southern Mediterranean countries. In order to mitigate the impact of this virus on human health, it is crucial to gain a deeper understanding beyond the anecdotal and fragmented evidence that currently exists. The aim of this study is to develop an amplicon-based whole genome sequencing method suitable for the genomic characterization of TOSV. Methods: Primers were designed on TOSV lineage A S, M and L segments reference sequences (GenBank: GCA_031497085.1) using Primal Scheme web tool to generate 400 bp tiled amplicons. To guarantee coverage and sensitivity, a multi-sequence alignment of GenBank-available complete sequences was used to identify mismatches and introduce degenerations in relevant ambiguous sites. Two-pool multiplex amplicon-based library preparation was carried out with Illumina Microbial Amplicon Prep (iMAP, Illumina) and custom designed primers. Two viral isolates on Vero E6 cells and three clinical samples of patients presenting with meningitis were sequenced. De novo assembly was performed with BaseSpace DRAGEN Targeted Microbial (version 1.3.1). Results: A set of 45 oligonucleotide primer pairs (26 for segment L, 13 for segment M and 6 for segment S) that amplify overlapping segments spanning TOSV genome was generated. The primers sets were subsequently compared to an alignment of 8 sequences for segment L, 16 for segment M and 32 for segment S to introduce degenerations. Genome sequencing yielded a mean 98.2% coverage for high-viral-titre propagates on Vero E6 cell culture. Two human samples (1 urine and 1 cerebrospinal fluid) with Ct (Cycle threshold) values of 32 and 33 yielded to sequences with coverage of 91.3% and 80.3%. Another urine sample with Ct = 35 yielded to 47% of mean coverage. Discussion: Our study, albeit with preliminary and limited but very promising results for propagates and samples with relatively high Ct values, proposes a new whole genome amplicon-based sequencing method for genomic characterization of TOSV one of the most neglected and least monitored arboviruses. Alongside an increasingly necessary systematic epidemiological monitoring of TOSV infections, WGS may be instrumental to unravel its genomic makeup and to gain insights into its biology and transmission dynamics. Conclusion: Taking advantage and making the most of the sequencing infrastructures, bioinformatics pipelines, and data-sharing platforms, established during the COVID-19 pandemic, it will make possible to establish an integrated surveillance led by sentinel territorial network to targeting TOSV and other endemic and emerging Arboviruses. This knowledge can inform the development of new diagnostics, therapeutics, and preventive measures, particularly in TOSV high risk regions.